Circulating Angiogenic Mediators in Patients with Moderate and Severe von Willebrand Disease: A Multicentre Cross-Sectional Study - Groeneveld, Dafna J.; Sanders, Yvonne V.; Adelmeijer, Jelle; Mauser-Bunschoten, Evelien P.; van der Bom, Johanna G.; Cnossen, Marjon H.; Fijnvandraat, Karin; Laros-van Gorkom, Britta A.P.; Meijer, Karina; Lisman, Ton; Eikenboom, Jeroen; Leebeek, Frank W.G. (Thrombosis and Haemostasis, 2018)
Inhibition of von Willebrand factor (VWF) expression in endothelial cells results in enhanced, possible dysfunctional angiogenesis, consistent with observations of severe gastrointestinal bleedings caused by vascular malformations in patients with von Willebrand disease (VWD). VWF is stored in endothelial Weibel–Palade bodies (WPB) with several other mediators of angiogenesis, like angiopoietin-2, osteoprotegerin and galectin-3. Increased release of angiopoietin-2 has been observed in medium of endothelial cells lacking VWF, but data on circulating levels of angiogenic factors in patients with VWD are lacking. The aim of this study was therefore to investigate plasma levels of angiogenic factors in patients with various types of VWD to obtain more insight into the pathogenesis of vascular malformations in these patients. We hypothesized that VWF deficiency leads to increased circulating levels of other WPB components. We therefore measured plasma levels of the WPB components angiopoietin-2, osteoprotegerin and galectin-3 as well as two other angiogenic factors (angiopoietin-1 and vascular endothelial growth factor [VEGF]) that are not stored within WPB. We observed that various angiogenic mediators are significantly different between types of VWD patients. Type 2A VWD patients had higher angiopoietin-1 levels compared with type 2B patients. Patients who have increased VWF clearance had higher angiopoietin-2 levels, whereas patients who have impaired VWF synthesis had higher galectin-3 levels. VEGF levels were negatively associated with VWF levels as type 3 VWD patients had the highest VEGF levels. However, complete VWF deficiency did not lead to increased circulating levels of other WPB components.
Keywords: von Willebrand factor; angiopoietins; angiodysplasia; vascular endothelial growth factor A; von Willebrand Disease